Honoring the name : a social-rhetorical approach to the Holiness Legislation (Lev 17-26) - Meyer, Esias E. (University of Pretoria, 2024)
Thesis (PhD (Old Testament and Hebrew Scriptures))--University of Pretoria, 2022.